Prevalence of left iliac vein compression in an asymptomatic population and patients with left iliofemoral deep vein thrombosis: A multicenter cross-sectional study in southern China. (September 2022) - Zhu, Qiaohua; Yang, Lun; Zhu, Huiyan; Kong, Wei; Feng, Ruizhi; Luo, Jun; Chen, Minming; Wu, Dehua; Yu, Qirong; Zhang, Ruyan; Luo, Meihua
Objective: Population-based epidemiological data on left common iliac vein (LCIV) compression is scarce. This study aimed to investigate the prevalence of LCIV compression in an asymptomatic population and patients with left iliofemoral deep vein thrombosis (IF-DVT). Materials and Methods: Nonprobability sampling method was used in this multicenter cross-sectional study. The minimum diameter of LCIV and right common iliac vein minimum were measured. The percentage of LCIV compression (LCIV-CP) was calculated. Compression severity (CS) was classified as mild (CP ≤ 50%), moderate (50% < CP ≤ 70%), and severe (CP > 70%). Results: In all, 896 subjects constituted the asymptomatic population and 93 patients constituted the IF-DVT population. In the asymptomatic population, LCIV-CP ranged from 1.1% to 89.9% (mean 44.0%), and people with mild, moderate, and severe CS accounted for 62.3%, 28.2%, and 9.5%, respectively. In the IF-DVT population, the mean LCIV-CP was 71.1% (range 42.2%–95.2%), and patients with severe CS accounted for 75.3%. Gender and age differences in LCIV-CP and CS distribution were observed in the asymptomatic population. Females, the young- and middle-aged group had higher LCIV-CPs. In the population with moderate-severe CS, the middle-aged group accounted for a larger proportion. Middle-aged females comprised the highest percentage of patients with moderate or severe CS. Sex and age affected the LCIV-CP and CS distribution. No gender and age differences were observed in the IF-DVT population. Conclusions: LCIV compression is common in population. Middle-aged females are the predominant population with moderate-severe compression. Overlapping of LCIV-CP in the asymptomatic and IF-DVT population is significant and other risk factors should be integrated into the consideration when assessing the risk of IF-DVT secondary to LCIV compression.